Effects of photoperiod on egg hatching and growth and survival of larvae fed with different diets in the Asian Catfish, Clarias macrocephalus (Günther) and the African Catfish, C. gariepinus (Burchell) - Mino, Samson A.; Metillo, Ephrime B.; Tobias, Ermelinda G. (2008)
Experiments were conducted in two Clarias species to determine the effects of: (1) photoperiod onegg fertilization and hatching, and (2) photoperiod and diet on larval growth and survival. Artificiallyfertilized eggs of C. macrocephalus and C. gariepinus exposed to combinations of different photope-riod regimes had similar fertilization rates (89–95%), but the highest hatching rates (70–76%) wererecorded at 6 h light (6L):18 h dark (18D) photoperiod and the shortest hatching time (24–25 h) undercontinuous light (24L:0D). Ten-day-old larvae of both species were reared for 35 d under differentphotoperiods and fed three types of diet. Clarias macrocephalus larvae were the largest (p < 0.05) andheaviest (p < 0.05) under 0L:24D photoperiod regardless of diet, but C. gariepinus larvae fed with dietsof chopped fresh shrimp (D2) or chopped fresh finfish (D3) and exposed to 0L:24D photoperiod weresignificantly the largest (p < 0.05) and heaviest (p < 0.05). The highest survival rates were observedunder photoperiods 18L:6D, 12L:12D and 0L:24D for C. macrocephalus and 12L:12D, 6L:18D, and 0L:24Dfor C. gariepinus. Survival rate was significantly higher in larvae fed diets D2 and D3 than those fed frymash alone (D1). In conclusion, short periods of light increased egg hatching rate but continuous lightshortened egg hatching time, while a combination of short periods of light and continuous darknessand fry mash supplemented with fresh feeds increased growth and survival of larvae in both catfishspecies.
Keywords: Catfishes